Time-Scale Shifting of Volatile Semiochemical Levels in Wild Type Lychnophora ericoides (Brazilian arnica) and Pollinator Records - Pavarini, Daniel Petinatti; Semir, João; Lopes, João Luís Callegari; da Silva, Ricardo Roberto; Lopes, Norberto Peporine (Planta Medica, 2020)
Lychnophora ericoides is a Brazilian folk phytomedicine from Cerradoʼs “campus rupestris”. Its volatile organic compounds includes bisabolene-derivatives as major compounds. Herein we provide the chemical profiling of constitutive volatile sesquiterpenes from L. ericoides leaves, timeframe emissions surveys, and pollinators records. In situ samples of L. ericoides were harvested. A headspace-solid phase micro extraction method of pre-concentration was optimized. Identification was done through GC-MS. Isolation and structural elucidation were performed whenever necessary. Pollinators were registered in pictures and video. Short time-series and harmonic regressions determined rhythms of single compounds, and average chromatographic signal area was used to determine mono and sesquiterpene rhythms. Concluding, optimized headspace-solid phase micro extraction method of terpenes level analysis was reached. α-Pinene, β-pinene, α-terpinene, para-cymene, limonene, γ-terpinene, terpinen-4-ol, dehydro-sesquicineole, and β-guaiene were identified using GC-MS data. 11-dehydro cadinol and ortho-acetoxy bisabolol were elucidated. Sesquiterpenes concentrations were higher due to temperature rise, lower leaf age, and flowering seasons. Harmonic regressions determined that daylight might control levels of terpenes. Hummingbird, hemiptera insects, and wasps were recorded visiting Compositae capitulum for the first time. We studied nondomestic plants from in situ conditions and concluded that bisabolene-derivative levels were more abundant than monoterpenes during flowering throughout the summer.
Keywords: Compositae; chemical profiling; headspace-SPME and GC-MS; Lychnophora ericoides; neotropical flora; pollinators; terpene emissions